Isolation and Characterization of Laccase from Trichoderma asperellum Tasjk65 - Kehe Fu; Lili Fan; Qi Li; Jiaming Ji; Zhenying Huang; Ting Huang (Biology)
Laccase catalyzes one-electron oxidation, producing water as the primary final product, thereby minimizing secondary environmental pollution. Consequently, it holds significant application potential in areas such as the degradation of toxic compounds. In this study, a high-laccase-producing Trichoderma strain was isolated from soil, and the conditions for laccase production were optimized. Additionally, the laccase-related gene was cloned, and its function was analyzed. The results revealed that the optimal conditions for laccase production in this strain were maltose as the carbon source, peptone as the nitrogen source, an optimal pH of 6.0, and an incubation time of 120 h, resulting in an enzyme activity of 1.32 U/mL. The purified enzyme exhibited a Michaelis constant (Km) of 0.06666 mmol/L when ABTS was used as the substrate. SDS-PAGE analysis indicated that the enzyme’s molecular weight was approximately 70 kDa. Sequencing of the target protein band led to the identification of the laccase-related gene Tasla01. Knockout of this gene resulted in the loss of laccase activity. We isolated a high-laccase-producing Trichoderma asperellum strain, Tasjk65, and cloned the laccase-related functional gene Tasla01. These findings lay a foundation for the source and application of laccase.